2004
DOI: 10.1562/be-03-28.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Inhibition and Enhancement of Luminol–H2O2–Co2+ Chemiluminescence by Phenolic Compounds and Amino Acids

Abstract: The effect of pH on inhibition and enhancement of luminol-H2O2-Co2+ chemiluminescence (CL) by 18 phenolic compounds and 20 amino acids was studied. It was found that most of the tested compounds showed an inhibiting effect at lower pH and an enhancing effect at higher pH. At a midrange pH, for some phenolic compounds with two ortho-position -OH, both an inhibiting and an enhancing peak were simultaneously observed. UV-visible spectra of the tested phenolic compounds at different pH values were studied. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
6
40
0
Order By: Relevance
“…The activity of a chemical enhancer, which is the most attractive mode for increasing the sensitivity, is strongly dependant upon pH of the CL reaction system [41,42]. Therefore, the effect of pH on CL reaction of L-012 was investigated.…”
Section: Optimization Of CL Conditionsmentioning
confidence: 99%
“…The activity of a chemical enhancer, which is the most attractive mode for increasing the sensitivity, is strongly dependant upon pH of the CL reaction system [41,42]. Therefore, the effect of pH on CL reaction of L-012 was investigated.…”
Section: Optimization Of CL Conditionsmentioning
confidence: 99%
“…In fact, it has been reported that some compounds either inhibit or enhance the luminol CL, depending on the pH of the solution. 23 With an increase in pH, inhibition for most compounds tended to convert toward enhancement. Furthermore, in the SIA methodology luminol was dissolved in dimethylformamide and sodium azide was dissolved in dimethylsulfoxide.…”
Section: Evaluation Of the Scavenging Capacity Against 1 O2mentioning
confidence: 99%
“…33,36,37 In this way, the quenching of CL by SIN was perhaps due to competition for superoxide anion between luminol and SIN, in which a hydroxyl was included.…”
Section: Analytical Applicationsmentioning
confidence: 99%